Lesson Study: analytic stance and depth of noticing in post-lesson discussions. Issue 4 (27th August 2019) - Karlsen, Anne Mette Færøyvik; Helgevold, Nina
Abstract : Purpose: The purpose of this paper is to shed light on teachers' attention to student learning in post-lesson discussions in Lesson Study (LS) by exploring the depth and analytic stance of noticing (van Es, 2011) and by identifying interactions that may extend or narrow the levels of noticing. Design/methodology/approach: The study has dug deeply into post-lesson discussions in the context of two different LS groups at a Norwegian lower secondary school. Findings: The paper provides empirical insights about crucial elements of teachers' learning processes pertaining to their professional noticing. Sharing of rich descriptions of evidence of student learning appeared to be a necessary foundation for the deepening of the teacher groups' analytic approach. The study highlights the importance of teacher groups' openness and attention to the collected data and a shared willingness to go deep into the interpretations. Interthinking and exploratory talk (Littleton and Mercer, 2013) are emphasised as important social interaction and talk modes to deepen the analytic stance and depth of noticing. Research limitations/implications: Even though this is a small study, it brings to light important knowledge about how interactions in post-research lesson discussions in LS can influence teachers' professional noticing. Practical implications: An implication of the study is to design observation forms that capture student learning as tools for teachers' professional noticing. Originality/value: This paper fulfils an identified need to investigate teachers' learning processes in LS, including how interactions within a teacher group influence noticing.